Environmentally relevant levels of λ-cyhalothrin, fenvalerate, and permethrin cause developmental toxicity and disrupt endocrine system in zebrafish (Danio rerio) embryo. (October 2017) - Zhang, Quan; Zhang, Yi; Du, Jie; Zhao, Meirong
Abstract: Synthetic pyrethroids (SPs) are one of the most widely used pesticides and frequently detected in the aquatic environment. Previous studies have shown that SPs posed high aquatic toxicity, but information on the developmental toxicity and endocrine disruption on zebrafish ( Danio rerio ) at environmentally relevant concentrations is limited. In this study, zebrafish embryos were employed to examine the adverse effects of λ-cyhalothrin (LCT), fenvalerate (FEN), and permethrin (PM) at 2.5, 10, 25, 125, 500 nM for 96 h. The results showed these 3 SPs caused dose-dependent mortality, malformation rate, and hatching rate. Thyroid hormone triiodothyronine (T3 ) levels were significantly decreased after exposure to LCT and FEN. Quantitative real-time PCR analysis was then performed on a series of nuclear receptors ( NRs ) genes involved in the hypothalamic–pituitary–gonadal (HPG), hypothalamic–pituitary–thyroid (HPT), hypothalamic–pituitary–adrenocortical (HPA) axes, and oxidative-stress-related system. Our results showed that LCT, FEN, and PM downregulated AR expression while upregulated ER1 expression, and caused alteration to ER2a and ER2b expression. As for the expression of TRα and TRβ, they were both decreased following exposure to the 3 SPs. LCT and PM downregulated the MR expression and FEN induced MR expression. In addition, the expression of GR was increased after treating with LCT, while it was suppressed after exposure to FEN and PM. The 3 SPs also caused various alterations to the expression of genes including AhRs, PPARα, and PXR . These findings suggest that these 3 SPs may cause developmental toxicity to zebrafish larvae by disrupting endocrine signaling at environmentally relevant concentrations. Highlights: The toxicity of these SPs to zebrafish embryos can be ranked as LCT > FEN > PM. The T3 content in larvae were both decreased after exposed to 500 nM LCT and FEN. The expressions of NRs genes caused by LCT, FEN and PM were disrupted.